The Effectiveness of Group Counseling with Self-Talk and Modeling Techniques to Increase Self-Efficacy of Pencak Silat Athletes - Yeni Puspita Sari; Edy Purwanto; Ali Murtadho (Jurnal Bimbingan Konseling, 2024)
Besides physical factors, self-efficacy is a mental factor which can significantly improve pencak silat or martial arts athletes. Regarding this issue, the present study aimed at examining the effectiveness of group counseling with the combination of self-talk and modeling techniques to increase the self-efficacy of pencak silat athletes. It used an experimental method with the design of randomized pretest-posttest comparison group and involved 24 athletes selected using random sampling who were further grouped into three to receieve the treatment of self-talk, modeling, and the combination of both techniques in form of counseling. The athletes data were analyzed using Wilcoxon, Kruskal Walis, and Mann Whitney tests. Based on the findings, it is concluded the group counseling with the combination of self-talk and modeling techniques can increase the athletes’ self-efficacy. Further implications and limitations are presented in the discussion section.